Association of stromal tumor-infiltrating lymphocytes with clinicopathological parameters in endometrial cancer - Sana Ahuja; Ashi Dubey; Sufian Zaheer (Korean Journal of Clinical Oncology)
Purpose Endometrial cancer (EC) ranks as one of the most prevalent gynecological malignancies globally. The presence and role of stromal tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment have garnered interest due to their prognostic and therapeutic potential. This study aimed to evaluate the association between stromal TILs and various clinicopathological parameters in EC. Methods A prospective study was conducted which included 30 histologically confirmed cases of endometrial carcinoma. Specimens collected from January 2023 to June 2024 were processed for routine histopathological examination and immunohistochemistry for CD3 and CD20 markers. TILs were quantified as per the International Immuno-Oncology Biomarker Working Group guidelines and categorized into low (<20%) and high (≥20%) TILs. Results The study comprised 30 female patients, predominantly aged 51 to 60 years. Most tumors were of the endometrioid subtype (93.3%). High TILs were significantly associated with early tumor stage, lower grade, lesser myometrial invasion, and absence of nodal involvement on univariate analysis and with lower tumor stage and grade on multivariate analysis. No significant association was found between TILs and age, lymphovascular, or perineural invasion. Conclusion The findings suggest that high TIL infiltration correlates with favorable tumor characteristics, potentially serving as a prognostic marker for early and less aggressive EC. High TILs were associated with better tumor stage, grade, and reduced nodal involvement, indicating their protective role in tumor progression. However, the lack of association with certain parameters calls for further investigation into the functional state of TILs and their interactions within the tumor microenvironment.